Strategi Pembelajaran PAUD di Masa Pandemi - Shidratul Attika; Sri Zulfida; Sri Devi Aryanti; Neneng Mayunes (TANJAK, 2021)
During the pandemic Covid 19, almost all levels of education use the online learning system. It takes a number of innovations from educators to enable the teaching and learning process during the pandemic runs smoothly. Innovations need to be done because there is a change in the learning process which is usually carried out directly (face to face), is currently switched to the online learning process. Fitting learning strategies are used with the intention that the learning process of early childhood students who are at the golden age still feels fun. The research objective is to determine the online learning strategies used by early childhood educators during the pandemic covid 19. This research uses a survey method with a qualitative approach. The sampling technique used is simple random technique. The research participants are 3 teachers at KB Ibnu Abbas Tanjungpinang and 5 teachers at RA Al Falah Tanjungpinang. The data collection technique is done by interview and documentation. The results show that in order for the online learning process to run well and be fun for children, good cooperation and communication between teachers and parents are needed. During the online learning process, teachers can take advantage of media such as whatsapp groups, voice notes and learning videos.